Analysis of the Impact of Stunting on Psychosocial Development in Pre-School Children in the Working Area Seberang Padang Community Health Center - Jumilia Jumilia; Cindy Cleodora; Monna Widyastuti (STIKep PPNI Jawa Barat, 2023)
Aims: This study aimed to determine the impact of stunting on psychosocial development in preschool children in terms of motoric, cognitive, affective, language, personality, moral spiritual, social the working area of the Seberang Padang Health Center in 2022. Method: Research’s type is quantitative with a descriptive research design. The sample population in this study were Children age 3-6 years who experienced stunting in the previous year in the Seberang Padang Health Center Work Area, totaling sample is 32 people. Sampling using the proportional random sampling method The instrument used is the evaluation of psychosocial development. Data analysis is univariate. Result: This research was conducted on preschool children (3-6 years), where there were 13 girls and 19 boys. This study shows that less than half of the respondents (46.7%) analyze the impact of stunting at risk on psychosocial development with the following details: more than half (53.1%) the impact of stunting is at risk on psychosocial (motor) development, less than half (46.7%) the impact of stunting has a risk on psychosocial (cognitive) development, less than half (31.2%) the impact of stunting has a risk on psychosocial (affective) development, and more than half (53.1%) the impact of a risk on psychosocial (language) development. at risk for psychosocial (social) development. Conclusion: addressing stunting and ensuring proper nutrition during pregnancy and early childhood is crucial for optimal child development and long-term well-being. Discussion: the leadership of the opposite Padang health center should provide education to mothers regarding nutritious food and psychosocial monitoring of preschool children at least once a month.